Pengembangan Lembar Kerja Peserta Didik Pembelajaran Lompat Jauh Gaya Menggantung Menggunakan Pendekatan Problem-Based Learnig: Developing Students Worksheet of Hanging Style Long Jump Learning Using The Problem-Based Learning Approach - Listiono, Bernaditya; Winarni, Sri (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study was to describe the development LKPD with PBL approach that is valid and practical. This study used the research method of developing a 4D model with test subjects in class X APHP 1 and X APL 1 at SMK N 1 Cangkringan, Sleman. The results of the teacher's practicality assessment after the LKPD applied in long jump learning in both classes met the practicality criteria with a very good category. The per- centage of students' practicality assessment of LKPD with a minimum category both in both classes fulfilled more than 80%. In class X APHP 1 as many as 100% of students stated that LKPD in the minimum category was good and in class X APL 1 as many as 93.55%. Thus LKPD hanging style long jump learning with PBL approach can be said to be valid and practical.